A speech act analysis of President Barack Obama’s selected speeches on healthcare / Samir Fadhil Thamir - Samir Fadhil , Thamir (2019)
This study aims to identify the different types of illocutionary acts and their functions in three selected speeches of the President Barack Obama on healthcare, which was later known as Obamacare. Searle’s (1979) theory of speech acts was applied as the theoretical framework to explore the types of illocutionary acts while Leech’s (1983) concept of illocutionary functions was used to examine the functions used. The selected speeches on healthcare, which were downloaded from The New York Times and Obama White House websites, were based on the highest viewers on YouTube. The qualitative analysis of the data suggests that Obama’s speeches were mainly composed of the assertive and the commissive acts, while the main functions were mostly collaborative and convivial. The findings also showed that similar sentences were used in different contexts such as the Congress and the House of Democrats, which mainly contained facts and promises. Further analysis revealed that promises were frequently used in Obama’s speech to Congress to gain support of other parties while he rarely used promises when he addressed the Democrats as they already support his healthcare programme. The results of the study suggest that political leaders and speech writers may consider using specific speech acts and functions to effectively convince target audience i.e., members of the Congress or the Democrats, to accept new ideas or changes to policies and programmes despite oppositions from other political parties.